Authenticity Assessment of (E)-Cinnamic Acid, Vanillin, and Benzoic Acid from Sumatra Benzoin Balsam by Gas Chromatography Combustion/Pyrolysis Isotope Ratio Mass Spectrometry - Deshou Mao; Liu Hong; Lei Fu; Zhiyu Li; Jianhua Chen; Chengming Zhang; Yiqin Wu; Wen Xiong; Jin Wang (International Journal of Analytical Chemistry)
Authenticity assessment of (E)-cinnamic acid, vanillin, and benzoic acid from various origins (n = 26) was performed using gas chromatography-isotope ratio mass spectrometry coupled with combustion and pyrolysis mode (GC-C/P-IRMS). For that reason, the above three compounds (1–3) from synthetic, natural, and Sumatra benzoin balsam (laboratory prepared, adulterated, and commercial) were investigated. The δ13CV-PDB and δ2HV-SMOW values for compounds 1–3 from synthetic samples (S1–S5) ranging from −26.9 to −31.1‰ and 42 to 83‰, respectively, were clearly different from those of authentic samples (N1–N4, L1–L9) varying from −29.8 to −41.6‰ and −19 to −156‰. In adulteration verification testing, for compounds 1 and 3, both δ13CV-PDB and δ2HV-SMOW data of A1 (5.0% added) and A2 (2.5% added) except A3 (0.5% added) fell into the synthetic region, whereas for compound 2, the δ2HV-SMOW data of adulterated samples (A1–A3) fell into the synthetic region, and even the lowest adulterated sample A3 is no exception. With this conclusion, some commercial Sumatra benzoin balsam samples were identified to be adulterated with synthetic 1 (C1, C3, and C5) and synthetic 2 (C3, C4, and C5) but not with synthetic 3. GC-C/P-IRMS allowed clear-cut differentiation of the synthetic and natural origin of 1, 2, and 3 and definite identification of whether a Sumatra benzoin balsam was adulterated or not.